The prevalence and associated factors of third-trimester pregnancy depression in pre-pregnancy overweight and obesity women: a cross-sectional study in Guangdong, China - Yao, Zheng; Zhou, Yanli; Chen, Jing; Liu, Xuantian; Li, Danying; Zhai, Jinguo (Frontiers in Public Health, 2025)
BackgroundThe third trimester of pregnancy is the most frequent period of prenatal depression. Its prevalence is associated with differences in weight status. Pre-pregnancy overweight and obesity (OWOB) pregnant women have a high risk of third-trimester pregnancy depression. The aim of this study was to investigate the depression status of pre-pregnancy OWOB women in the third trimester of pregnancy, and to explore the influence of modifiable lifestyle behaviors during pregnancy on their depression status, so as to provide scientific basis for the prevention and intervention of third-trimester pregnancy depression in OWOB pregnant women.MethodsA cross-sectional survey was conducted among 441 pregnant women with pre-pregnancy OWOB recruited from two tertiary hospitals in Guangdong Province. Participants completed a basic information form, the Self-Rating Depression Scale, the Food Frequency Questionnaire, the Perinatal Pregnant Women’s Health Literacy Scale, the Physical Activity Rating Scale, and the Pittsburgh Sleep Quality Index. Binary logistic step regression was used to identify the associated factors of pregnancy depression in the third trimester.ResultsAmong the 441 participants, 411 (93.20%) were overweight and 30 (6.80%) were obesity prior to pregnancy. The mean score of depression was 48.50 ± 9.48. A total of 289 (65.53%) women had no depression, while 107 (24.26%) had mild, 44 (9.98%) had moderate, and 1 (0.23%) had severe depression. Binary logistic regression analysis showed that educational level, career, family income, and first pregnancy or not were the influencing factors for third-trimester pregnancy depression among pre-pregnancy OWOB women. The balanced dietary pattern, higher physical activity level and health literacy were protective factors, while the highly processed dietary pattern and sleep disorders were risk factors (p < 0.05).ConclusionAbout one-third of pre-pregnancy OWOB pregnant women experienced depression in the third trimester of pregnancy. The depression was most likely associated with modifiable lifestyle behaviors. Although the cross-sectional design may not necessarily indicate a cause-effect relationship, the findings suggest that early lifestyle interventions may still be an effective strategy for improving mental health outcomes in this high-risk population.